The role of microstructure in fatigue crack initiation and propagation in 9-12Cr ferritic-martensitic steels - Batista, Maria Natalia (2014)
The present paper presents low-cycle fatigue results about cyclic behaviour, the evolution of the dislocation structure and the nucleation and propagation of microstructural cracks in commercial ferritic-martensitic steel AISI 410.